Społeczności wirtualne bibliotekarzy w Polsce - Majewska , Paulina (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The article discusses how librarians are using social networking sites in Poland. It describes the largest polish librarian’s virtual communities and shows them as a tool that can be helpful in librarian’s work. Librarian comprise a special professional group that is evolving very fast. The reason is the fast progress of technology and internet network that have reached the polish libraries. Virtual communities are the source of professional knowledge where librarians can discuss their professional matters and integrate. This professional virtual communities are expanding and concentrate more users every day. Internet is now one of the most important communication platform for polish library workers.